Analisis Berpikir Pseudo Dalam Memecahkan Masalah Matematika - Hanani Yun Indri; Erni Widiyastuti (AlphaMath : Journal of Mathematics Education, 2018)
The study aims to find out pseudo-thinking in solving mathematical problems. The methods used in this study are qualitative descriptive. The research subject is junior high school students using the purposive sampling technique, the students are grouped into three ranks i.e. low, medium and high rankings which each ranked 3 students as respondents. The total number of respondents was 9 students. Data collection techniques using tests, interviews, and documentation. From the results of the study gained that: 1) students who are ranked low in solving mathematical problems are experiencing pseudo-analytic or pseudo-false, 2) students who are in the moderate level also experience pseudo-analytic or pseudo-incorrect, 3) students who are in high ranking experience pseudo-analytic and pseudo-4) students who experience pseudo-thinking choose procedures using their own reasoning and convince it as a correct understanding , so there is no attempt to re-examine what he has done